PELAKSANAAN BAURAN PROMOSI PAKET WISATA PADA DWIDAYATOUR PEKANBARU - Andira, Husnul Anisa; ', Etika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research discusses the implementation of the promotional mix for tour packages at Dwidayatour Pekanbaru. The aim of the research is to find out the promotional strategies carried out by Dwidayatour and the dominant promotional activities they carry out. With the rapid growth of the travel agency sector in Pekanbaru, promotional strategies are important to reach wider consumers. This research uses a qualitative descriptive method through interviews and direct observation at the Dwidayatour Pekanbaru office. The concepts used include tourism, travel agencies, tour packages, marketing and promotional mix. The research results show that Dwidayatour has implemented a promotional mix according to the concept, but still faces obstacles in reaching areas outside Pekanbaru optimally. Nevertheless, promotional activities continue to be carried out consistently to expand consumer reach. Keywords: Promotional Mix, Tour Packages, Dwidayatour Pekanbaru